The Impact of M&A on Company Performance - Mao, Qi (2018)
During the last decades, scholars and researchers cannot reach a consensus on whether M&A can exert favourable impacts on company performance. Regarding the issue, this paper selects sample data from 81 UK takeover deals that are announced and completed from 2010 to 2013. Benchmarks adjusted return on assets and operating margin are regarded as the performance measures and are utilized to evaluate the change of profitability caused by acquisitions. We compare the premerger and postmerger performance and test the relation between some possible deal- and firm-specific influencing factors and performance measures through cross-sectional regression analysis. Empirical results show that on the aggregate level, acquirers may experience persistent decline in BAROA but slight growth in BAOM. However, these impacts seem to be small and insignificant. Moreover, regardless of the variation direction of operating performance, up or down, implications would last only for two or three years. In addition, inferior acquirers tend to become better after M&A while superior firms may present a deterioration beyond expectation. The regression outcome reveals method of payment and per-acquisition performance relative to benchmarks are significant determinants in affecting the degree of change in BAROA while target status is the sole factor in BAOM.